(untitled) (MAUSAM, 1962)
An electronic equipment for mass calibration of chronometric radiosonde has been described. Instead of measuring the linear displacements recorded on the chart, the reference contact of the radiosonde has been utilized to open an electronic gate and the element contact to close it. The duration of the gate is measured by pulses derived from a standard oscillator. Three gates are employed for each radiosonde, one each for pressure, temperature and humidity. Compact and versatile and with 72 channels, the equipment is capable of calibrating 24 radiosondes at a time, saving manpower and spaoe.